2022
DOI: 10.3390/vaccines10060843
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Enterovirus A71 in Surveillance of Acute Flaccid Paralysis Cases in Senegal, 2013–2020

Abstract: Enterovirus A71 (EV-A71) is a non-polio enterovirus that currently represents a major public health concern worldwide. In Africa, only sporadic cases have been reported. Acute flaccid paralysis and environmental surveillance programs have been widely used as strategies for documenting the circulation of polio and non-polio enteroviruses. To date, little is known about the molecular epidemiology of enterovirus A71 in Africa where resources and diagnostic capacities are limited. To fill this gap in Senegal, a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…At present, most mouse models are primarily used to evaluate the protective effects of CVB1 vaccines against virus-induced T1DM. In previous research, the RD cell-adapted strain 204 showed strong tropism to the pancreas, but no damage to the heart, brain, liver, limb muscle, and kidney was observed, and in moribund mice, a positive signal was only observed in the heart and spinal cord (Ndiaye et al, 2022 ). In the present study, histopathology and IHC analyses and tissue viral RNA detection indicated that the KM7-X29 strain had stronger tropism to the pancreas, brain, and liver.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…At present, most mouse models are primarily used to evaluate the protective effects of CVB1 vaccines against virus-induced T1DM. In previous research, the RD cell-adapted strain 204 showed strong tropism to the pancreas, but no damage to the heart, brain, liver, limb muscle, and kidney was observed, and in moribund mice, a positive signal was only observed in the heart and spinal cord (Ndiaye et al, 2022 ). In the present study, histopathology and IHC analyses and tissue viral RNA detection indicated that the KM7-X29 strain had stronger tropism to the pancreas, brain, and liver.…”
Section: Discussionmentioning
confidence: 88%
“…The previous study also found differences in cross-neutralization between the 10 EV-A71 sub-genotypes tested; a C4 genotype EV-A71-based vaccine elicited a powerful cross-neutralization response against other EV-A71 C4 genotypes, and the cross-neutralization of genotype A (EV-A71 prototype strain) was the least efficient. As EV-A71, which included one serotype, five genotypes, and ten sub-genotypes (McMinn, 2012 ; Ndiaye et al, 2022 ), CVB1 has one serotype and eight genotypes, although the GII genotype is the most common among them in China. In addition, we found that the antiserum against our inactivated CVB1 vaccine could not efficiently neutralize the CVB1 prototype strain Conn-5, which requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…We reported only eight cases of EVA71 in 2022; all were mild and without neurologic manifestations. In a Senegalese study by Ndaye et al in 2022, a low number of isolates tested positive for EVA71 (9 out of 521 NPEV isolates) [31]. While a recent study from South Vietnam reported the predominance of EVA71 as the etiological agent of HFMD, AFP and enteroviral meningitis [32].…”
Section: Discussionmentioning
confidence: 96%